Everyday life under the PIDE: A quantitative survey on the relations between ordinary citizens and Salazar’s political police (1955–74) - Simpson, Duncan (2021)
This article examines the relations between Portuguese society and Salazar’s political police (PIDE) from the perspective of the everyday lives of ordinary citizens – in contrast to the small minority of oppositionists that has so far monopolized the attention of historians. It is based on a quantitative survey of 400 respondents in four separate locations across Portugal and addresses two main research questions: To what extent did the sample of ordinary citizens experience the PIDE as a disruptive influence on their daily lives? Was the PIDE ‘normalized’ by them as part of the framework of everyday life? The data analysis calls upon the inputs of the international bibliography of everyday life under dictatorship and critically engages with the existing historiography of the PIDE.